Evidence for adaptive divergence of thermal responses among Bemisia tabaci populations from tropical Colombia following a recent invasion. (6th May 2014) - Díaz, F.; Muñoz‐Valencia, V.; Juvinao‐Quintero, D. L.; Manzano‐Martínez, M. R.; Toro‐Perea, N.; Cárdenas‐Henao, H.; Hoffmann, A. A.
Abstract There is an increasing evidence that populations of ectotherms can diverge genetically in response to different climatic conditions, both within their native range and (in the case of invasive species) in their new range. Here, we test for such divergence in invasive whitefly Bemisia tabaci populations in tropical Colombia, by considering heritable variation within and between populations in survival and fecundity under temperature stress, and by comparing population differences with patterns established from putatively neutral microsatellite markers. We detected significant differences among populations linked to mean temperature (for survival) and temperature variation (for fecundity) in local environments. A QST − FST analysis indicated that phenotypic divergence was often larger than neutral expectations (QST > FST). Particularly, for survival after a sublethal heat shock, this divergence remained linked to the local mean temperature after controlling for neutral divergence. These findings point to rapid adaptation in invasive whitefly likely to contribute to its success as a pest species. Ongoing evolutionary divergence also provides challenges in predicting the likely impact of Bemisia in invaded regions.